Nicotine withdrawal alleviates acetic acid-induced gastric injury in rats - YEGEN, BERRAK; ÇETİNEL, ŞULE (ELSEVIER SCIENCE BV, 2009)
Epidemiological and experimental studies have demonstrated that cigarette smoking intensifies gastric ulceration. Although nicotine can act as an anxiolytic and antidepressant, its withdrawal may also lead to increased anxiety and depression. In order to associate the toxic actions of nicotine on gastric mucosa with alterations of anxiety level and to evaluate the impact of nicotine withdrawal on the anxiety level and the severity of ulcer, an acetic acid-induced ulcer model was used. Male Sprague-Dawley rats were given either tap water or nicotine bitartarate (50 mu g/ml in drinking water) for 15 days, while another group of rats had 5 clays of withdrawal following 10 days of nicotine treatment. Ulcer was induced by acetic acid on the 15th day of the treatments, and the rats were followed for 3 days until they were decapitated and the gastric tissues were obtained. Using the hole-board test, basal anxiety levels measured on the first day of the treatments were compared with the measurements made at the early and late phases of ulcer induction. Chronic administration of nicotine did not have a potentiating effect on acetic acid-induced gastric ulcer, since the gastric injury, as assessed by both macroscopic and microscopic evaluation and increased gastric myeloperoxidase activity indicating neutrophil recruitment, was not exaggerated or attenuated by nicotine intake. On the other hand, nicotine withdrawal attenuated gastric mucosal injury, despite an increased level of anxiety. Smoking cessation, which triggers the onset of depressive symptoms with nicotine withdrawal, still has a worthwhile positive effect on the gastric mucosa. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Gastric ulcer; Nicotine; Anxiolytic; Neutrophil accumulation; CIGARETTE-SMOKING; PROSTAGLANDIN E(2); MUCOSAL LESIONS; ULCER; STOMACH; ANXIETY; STRESS; ANGIOGENESIS; PATHOGENESIS; DECREASES